2020
DOI: 10.1016/j.metop.2020.100026
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated ghrelin stimulates fatty acid oxidation to protect skeletal muscle against palmitate-induced impairment of insulin action in lean but not high-fat fed rats

Abstract: Background Ghrelin is a gut hormone that spikes in circulation before mealtime. Recent findings suggest that both ghrelin isoforms stimulate skeletal muscle fatty acid oxidation, lending to the possibility that it may regulate skeletal muscle’s handling of meal-derived substrates. It was hypothesized in the current study that ghrelin may preserve muscle insulin response during conditions of elevated saturated fatty acid (palmitate) availability by promoting its oxidation. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Our results support the idea that the CRF family regulates or mediates the ghrelin isoforms' effects on muscle metabolism. A recent study supports our findings in showing that a decline in CRF-R2 levels in soleus muscle isolated from high-fatfed rats resulted in inhibition of the palmitate oxidation stimulated by ghrelin (Cervone et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results support the idea that the CRF family regulates or mediates the ghrelin isoforms' effects on muscle metabolism. A recent study supports our findings in showing that a decline in CRF-R2 levels in soleus muscle isolated from high-fatfed rats resulted in inhibition of the palmitate oxidation stimulated by ghrelin (Cervone et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies that support our findings have shown that in isolated muscles from rats, des-acyl ghrelin increases fatty acid oxidation in vitro (Cervone et al, 2020;Kraft et al, 2019). Furthermore, under high fatty acid conditions, des-acyl ghrelin protects isolated mature rat skeletal muscle from insulin resistance by activating the AMP-activated protein kinase/ACC axis, resulting in increased oxidation of fatty acids (Cervone et al, 2020). It is important to note that while those studies found that des-acyl ghrelin increases fatty acid oxidation (Cervone et al, 2020;Kraft et al, 2019), the present study found increased fat accumulation in C2C12 cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations